A General Method to Access Underexplored Ylideneamino Sulfates as Interrupted Beckmann-Type Rearrangement Intermediates - Yifei Zhou; Alan M. Jones (Molecules, 2024)
The Beckmann rearrangement of ketoximes to their corresponding amides, using a Brønsted acid-mediated fragmentation and migration sequence, has found wide-spread industrial application. We postulated that the development of a methodology to access ylideneamino sulfates using tributylsulfoammonium betaine (TBSAB) would afford isolable Beckmann-type intermediates and competent partners for subsequent rearrangement cascades. The ylideneamino sulfates generated, isolated as their tributylammonium salts, are sufficiently activated to undergo Beckmann rearrangement without additional reagent activation. The generation of sulfuric acid in situ from the ylideneamino sulfate giving rise to a routine Beckmann rearrangement and additional amide bond cleavage to the corresponding aniline was detrimental to reaction success. The screening of bases revealed inexpensive sodium bicarbonate to be an effective additive to prevent classic Brønsted acid-mediated fragmentation and achieve optimal conversions of up to 99%.